Problematyka naukowo-badawcza i dorobek naukowy pracowników Katedry Pedagogiki i Dydaktyki Uniwersytetu Poznańskiego 1919–1939 w stulecie powstania Uniwersytetu im. Adama Mickiewicza w Poznaniu (1919–2019) - Nowak-Kluczyński, Konrad (Biuletyn Historii Wychowania, 2019)
Research issues and academic achievements of the faculty of the Department of Pedagogy and Teaching at Poznań University in 1919–1939 on the centennial of the establishment of Adam Mickiewicz University in Poznań (1919–2019). In its early days, Poznań University attracted a large number of researchers representing many disciplines of science but prevailing humanities. Poznań was a centre of very dynamic research into pedagogy and psychology. Initially, the Department of Pedagogy and Teaching at Poznań University focused on just a few research fields and areas. In the lead were issues related to the theory of upbringing, educating adults and the history of upbringing. In the local Department of Pedagogy and Teaching, a number of contributions was made to teaching and the methodology of some teaching subjects. In the Interwar Period, the following research areas were pursued by the pedagogy teachers at Poznań University: Antoni Danysz’ progressive-national trend referring to the ideological traditions of the Revolutions of 1848; Ludwik Jaxa-Bykowski’s nationalist-anthropological trend resulting from nationalist conflicts and efforts to reinforce the nation with special emphasis placed on the first decade of Poland’s independence; Marian Wachowski’s nationalist-imperialistic trend based on German philosophical pedagogy.